The Effect of Literacy Skills on the Critical Thinking Skills of Mathematics Education Students - Vera Dewi Susanti; Ika Krisdiana (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to see the effect of literacy skills on students' critical thinking skills. This research type is a correlational study to know the relationship between literacy skills and students' critical thinking skills. The total population is 168 students, and the level of precision is set at 10%. A sample of 63 respondents will be obtained, taken using a simple random sampling technique. The data analysis used in this study is a simple regression analysis with the product-moment correlation coefficient formula. The results showed that literacy skills positively correlate with students' critical thinking skills by 80%. It shows that besides literacy, there are still 20% of other factors that can affect students' critical thinking skills.